A Meta-Analysis of Changes in Brain Activity in Clinical Depression - Palmer, Susan M.; Crewther, Sheila G.; Carey, Leeanne M.; , The START Project Team (Frontiers in Human Neuroscience, 2015)
Insights into neurobiological mechanisms of depression are increasingly being sought via brain imaging studies. Our aim was to quantitatively summarize overlap and divergence in regions of altered brain activation associated with depression under emotionally-valenced compared to cognitively-demanding task conditions, with reference to intrinsic functional connectivity. We hypothesized differences reflective of task demands. A coordinate-based meta-analysis technique, Activation Likelihood Estimation (ALE), was used to analyze relevant imaging literature. These studies compared brain activity in depressed adults relative to healthy controls during three conditions: (i) emotionally-valenced (cognitively easy) tasks (n=29); (ii) cognitively-demanding tasks (n=15); and (iii) resting conditions (n=21).The meta-analyses identified 5, 8 and 7 significant clusters of altered brain activity under emotion, cognition and resting conditions respectively in depressed individuals compared to healthy controls. Regions of overlap and divergence between pairs of the three separate meta-analyses were quantified. There were no significant regions of overlap between emotion and cognition meta-analyses, but several divergent clusters were found. Cognitively-demanding conditions were associated with greater activation of right medial frontal and insula regions while bilateral amygdala was more significantly altered during emotion (cognitively-undemanding) conditions; consistent with task demands.Overlap was present in left amygdala and right subcallosal cingulate between emotion and resting meta-analyses, with no significant divergence.Our meta-analyses highlight alteration of common brain regions, during cognitively-undemanding emotional tasks and resting conditions but divergence of regions between emotional and cognitively-demanding tasks. Regions altered reflect current biological and system-level models of depression and highlight the relationship with task condition and difficulty.